Genetic Polymorphisms in Patients with Epilepsy: A Mini Review. - Kleber Santiago Freitas e Silva (International Epilepsy Journal, 2018)
Epilepsy comprises a series of chronic neurological disorders characterized by recurrent seizures. Over 50 million people are affected by epilepsy worldwide. In addition, genetic components capable of predicting epilepsy predisposition and antiepileptic drugs response would lead to the development of promising treatment and a better prognosis of the disease. Several genes and their variants have been investigated whether they could affect the onset of epilepsy. The brain-derived neurotrophic factor gene, the ATP-binding cassette subfamily B member and the cytochrome P450 are the most common polymorphic genes related to epilepsy. Early identification of risk factors for epilepsy should optimize treatment and prognosis. The characterization of genetic polymorphism contribute to the selection of the most promising antiepileptic therapy and avoidance of drug resistance. The development of biomarkers to estimate the risk of epilepsy and drug resistance would have a clinical impact on the treatment of the disease and on anti-epileptic drug therapy.
Keywords: Epilepsy